THE EFFECT OF INDIVIDUAL AND ORGANIZATIONAL STRESSOR ON THE EMPLOYEES PERFORMANCE - Agustina, Granit; Suprianto Ahmadi, Rudi; Suryani, Herni; Darmawan, Arief; Febrian, Feby (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to evaluate the effects of individual stressors and organizational stressors on employee performance in one of the state-owned banks in Bandung. Performance is one important factor in assessing the success of an organization. One effort to improve employee performance is to pay attention to work stress conditions, which include individual stress caused by the workplace and organizational stress that comes from oneself. The research method used is descriptive and verification. The sampling technique uses census techniques. The collection of primary research data using 70 questionnaires. The secondary data used comes from a variety of literature and sources that are relevant to research. Data analysis was performed by path analysis. The Results Showed that individual stressors and organizational stressors simultaneously had a significant effect on employee performance by 84.5%, This was evidenced by the F test. Showed a significance value of 0.000, less than 0.05. T-test results indicate that individual and organizational stressors partially Affect employee performance. This is evidenced by the t-test, which shows the significant value of all independent variables is less than 0.05, which is equal to 0.000 for individual stressors variables, and 0,